Сучасний стан і пeрспективи активного туризму в Українських Карпатах - Луцький, Василь; Lutkyi, Vasyl (Волинський національний університет імені Лесі Українки, 2010)
У статті розглянуто основні напрями розвитку активного туризму в Українських Карпатах. Проаналізовано форми туристично-краєзнавчої роботи й подано перспективи активного туризму в Карпатах. The main trends of active tourism development in the Ukrainian Carpathians are indicated in the article. The forms of touristic and regional studies are analyzed and the perspectives of active tourism in the Carpathians are given.
Current State and Perspectives of Tourism in the Ukrainian Carpathians
Keywords: активний туризм; туристські заходи; туристсько-краєзнавча робота; active tourism; touristic and regional studies; tourism activities